An efficient isolation method for meiotic mutants causing meiotic nondisjunction or elevated recombination frequency in Neurospora crassa. - K. Hasunuma; K. Furukawa (Fungal Genetics Reports, 1982)
An efficient isolation method for meiotic mutants causing meiotic nondisjunction or elevated recombination frequency in Neurospora crassa.